Requirement Specification to Develop Digital Health Promotion Platform for Millenial and Post-Millenial Generations in Surabaya Indonesia - Atik Qurrota A’Yunin Al-Isyrofi; Sri Widati; Rachmat Hargono (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Surabaya is facing various urban problems that are increasingly complex. Therefore,innovative solutions are needed such as digital health promotion for millenial and post-millenial as thelargest segment of internet users. The aim of this study is to identify the requirement specification to developdigital health promotion platform for millenial and post millenial generations in Surabaya.Methods: This research used qualitative methods with case study approach. This study used purposefulsampling on 24 informants, consists of several related parties who met the criteria. Data collection techniquewas carried out through in-depth interview and documents review.Results: The requirement specifications were classified into 4 domains (functional, technical, interface,performance requirements). Functional requirements consist of procedures, menus, features, content, data,information, control mechanism, and parties involved. Technical requirements include programs, networks,size, and types of digital devices. Interface requirements consist of visual display related to user interfaceand operating system. Performance requirements include several aspects such as speed, accuracy, efficiency,effectiveness, security, etc.Conclusion: Digital health promotion platform requirement specification must be tailored to the needs ofmillenial and post-millenial generations. If these requirements can be met, the target will be easier to acceptand use digital health promotion platform.